Opinions of Medical Staff Regarding Antibiotic Resistance - Aneta Krolak-Ulińska; Piotr Merks; Urszula Religioni; Beata Chełstowska; Agnieszka Drab; Krystian Wdowiak; Katarzyna Plagens-Rotman; Zbigniew Doniec; Anna Staniszewska (MDPI AG, 2024)
Introduction: Antibiotic resistance poses a significant threat to public health, that can lead to reduced effectiveness of many therapies, increased morbidity, longer hospitalization times, increased deaths, and additional costs for health care systems. Unreasonable use of antibiotics may result from a lack of adequate knowledge about antibiotic therapy and a lack of knowledge of the risks associated with antibiotic resistance, both among medical personnel and patients. Aim. The primary objective of the study was to verify the opinion of medical personnel on the risks associated with antibiotic resistance. Material and Methods: The study was conducted in 2023 among 605 Polish sanitary workers. An anonymous survey designed specifically for the purpose of the study was used. The survey was made available on the Internet through the Trade Unions of Pharmacy Workers and directly to hospitals with the support of local authorities. Results: The majority of respondents were women (77.36%). The largest group consisted of individuals over 40 years of age (55.04%). More than half of the respondents were nurses (56.20%), and every fourth of the respondents was a physician (23.64%). Most respondents consider antibiotic resistance to be a very serious (24.13%) or extremely serious (30.75%) problem. The problem of antibiotic resistance on a global scale was mentioned, especially in the opinions of physicians and nurses (p < 0.01), people working in the profession for over a year (p < 0.01), and people with a specialization or undergoing specialist training (p = 0.00). Similarly, these groups most often indicated that antibiotic resistance poses a problem in their workplace. The main problems of antibiotic resistance were the use of antibiotics in farm animals (36.69%), the pressure on patients to take antibiotics (38.84%), and the prophylactic use of antibiotics (43.15%). Conclusions: Medical personnel consider antibiotic resistance a somewhat serious problem, although not all agree in this regard. The risk of antibiotic resistance is much more seriously assessed by physicians and nurses, as well as by people with specializations or undergoing specialization training. Knowledge about antibiotic resistance should be further spread among all groups of medical personnel.